IMPLIKASI PROGRAM MAKANAN BERGIZI GRATIS TERHADAP FOKUS BELAJAR DI SD SDN 060913 KECAMATAN MEDAN TEMBUNG - Cindy Pratiwi; Nina Akbar; Christin Angelita Sianturi; Winara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Focus on learning for elementary school students is crucial for achieving optimal learning outcomes. However, many elementary school students struggle to focus on their studies due to a lack of nutritional information. The Free Nutritious Meals (MBG) program is expected to help improve student focus. This study aims to analyze the impact of the MBG program on elementary school students' focus on learning. This study used a quasi-experimental design with a sample of 60 elementary school students who received the MBG program. Data were collected through questionnaires and observations. The results indicate that the MBG program has both positive and negative impacts on elementary school students' focus on learning. The MBG program can be a strategy for improving elementary school students' focus on learning. Therefore, a broader and more effective implementation of the MBG program is needed.